Peripheral nerve blocks of wrist and finger flexors can increase hand opening in chronic hemiparetic stroke - Dewald, Hendrik A.; Yao, Jun; Dewald, Julius P. A.; Nader, Antoun; Kirsch, Robert F. (Frontiers in Neurology, 2024)
Introduction Hand opening is reduced by abnormal wrist and finger flexor activity in many individuals with stroke. This flexor activity also limits hand opening produced by functional electrical stimulation (FES) of finger and wrist extensor muscles. Recent advances in electrical nerve block technologies have the potential to mitigate this abnormal flexor behavior, but the actual impact of nerve block on hand opening in stroke has not yet been investigated. Methods In this study, we applied the local anesthetic ropivacaine to the median and ulnar nerve to induce a complete motor block in 9 individuals with stroke and observed the impact of this block on hand opening as measured by hand pentagonal area. Volitional hand opening and FES-driven hand opening were measured, both while the arm was fully supported on a haptic table (Unloaded) and while lifting against gravity (Loaded). Linear mixed effect regression (LMER) modeling was used to determine the effect of Block. Results The ropivacaine block allowed increased hand opening, both volitional and FES-driven, and for both unloaded and loaded conditions. Notably, only the FES-driven and Loaded condition’s improvement in hand opening with the block was statistically significant. Hand opening in the FES and Loaded condition improved following nerve block by nearly 20%. Conclusion Our results suggest that many individuals with stroke would see improved hand-opening with wrist and finger flexor activity curtailed by nerve block, especially when FES is used to drive the typically paretic finger and wrist extensor muscles. Such a nerve block (potentially produced by aforementioned emerging electrical nerve block technologies) could thus significantly address prior observed shortcomings of FES interventions for individuals with stroke.